2022
DOI: 10.31471/2415-3184-2021-2(24)-35-46
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness, Knowledge, Attitude and Perception on Microplastics Pollution Around Lagos Lagoon

Abstract: Microplastic pollution is now globally flagged as a foremost menace to livelihoods, biodiversity, and public health due the pervasive nature of plastic wastes, poor knowledge of its ecological impact and poor attitude towards sustainable waste management practices. Hence, this paper explores public awareness, knowledge, attitude and perception on Microplastic pollution and its ecological health implication through a survey data collected from residents, students, fishermen and local tourist around Lagos Lagoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Positive attitude such as willingness to share safety information about issues of public health concern, and community participation in public health programs are widely considered as positive indicators to achieving a sustainable healthy environment (Omoyajowo et al, 2021, Omoyajowo et al, 2023. Similar study observed similar great attitude in public willingness to co-operate with the government on mitigation efforts towards reducing Microplastic pollution (Alkyildiz et al, 2015, Omoyajowo et al, 2021a. The public may utilize different information sources to learn about new and emerging health risks via internet, social media, government agencies, etc.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Positive attitude such as willingness to share safety information about issues of public health concern, and community participation in public health programs are widely considered as positive indicators to achieving a sustainable healthy environment (Omoyajowo et al, 2021, Omoyajowo et al, 2023. Similar study observed similar great attitude in public willingness to co-operate with the government on mitigation efforts towards reducing Microplastic pollution (Alkyildiz et al, 2015, Omoyajowo et al, 2021a. The public may utilize different information sources to learn about new and emerging health risks via internet, social media, government agencies, etc.…”
Section: Discussionmentioning
confidence: 74%
“…(Ogunyebi et al, 2019, Omoyajowo et al, 2024. Within this foregoing context is the discourse on emerging contaminants (ECs), also known as contaminants of emerging concerns (CECs) (Dulio et al, 2018, Omoyajowo et al, 2021a. ECs could be described as a group of natural and synthetic chemicals and chemical metabolites which are presently not monitored in the environment but are perceived to portend a high threat to the health of human and other ecological receptors (Geissen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 41% of the respondents fell into this category, and an even more significant majority, surpassing 63%, believed that the government is responsible for controlling MPs. This lack of awareness was more pronounced among educated populations, with social media identified as the primary source for self-education, a finding presented by [87]. In a similar survey, ref.…”
Section: Public Awareness Campaignsmentioning
confidence: 89%
“…Table 2 shows the likely sources of the pollutants. It has been established that burning of fossil fuels, industrial waste, combustion of plastic and organic products, incomplete combustion of synthetic substances and a number of other anthropogenic factors negatively affect air quality (Adams and Kanaroglou, 2016;Ebuete et al, 2019;Koleayo et al, 2021;Omoyajowo et al, 2022;Glory et al, 2023). Ogui New Layout is heavily populated with lots of existing and upcoming industries.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%